2021
DOI: 10.3390/ijerph18020673
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Knowledge, Perception, and Practices among Domestic Visitors to the Prophet’s Mosque in Al Madinah City Amid the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: This study aimed to assess hand hygiene knowledge, perception, and practices of visitors to the Prophet’s Mosque in Al Madinah City, Saudi Arabia. Using a self-administered electronic questionnaire, a cross-sectional survey was conducted among domestic residents, who visited the mosque between 31 July and 3 August 2020. Participants’ demographic data, hand hygiene knowledge, perception, and practices were collected. Four hundred participants aged 18–65 (median 36) years completed the survey, of which 215 (53.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
(43 reference statements)
3
17
1
Order By: Relevance
“…The fact that most participants reported distancing themselves from these behaviors indicates a positive attitude and practice that may assist in combating COVID-19. The rates reported in the current study were higher than those of a previous Saudi survey, which found that its participants demonstrated some knowledge gaps and negligence in hand hygiene practice ( 46 ). The majority of the current study stated that they wore face masks in public, although this was not required during the data collection period.…”
Section: Discussioncontrasting
confidence: 87%
“…The fact that most participants reported distancing themselves from these behaviors indicates a positive attitude and practice that may assist in combating COVID-19. The rates reported in the current study were higher than those of a previous Saudi survey, which found that its participants demonstrated some knowledge gaps and negligence in hand hygiene practice ( 46 ). The majority of the current study stated that they wore face masks in public, although this was not required during the data collection period.…”
Section: Discussioncontrasting
confidence: 87%
“… 48 Moreover, hand washing with soap and water are routinely practiced in religious institutions to prevent the current pandemic. 49 …”
Section: Discussionmentioning
confidence: 99%
“…48 Moreover, hand washing with soap and water are routinely practiced in religious institutions to prevent the current pandemic. 49 In chronic disease patients, health literacy is one of the main determinant factors for execution of COVID-19 preventive behaviors. 50 Our study revealed that patients with low literacy were more likely to have low perception about the efficacy of COVID-19 prevention methods compared to more educated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Saudi MoH implemented the economic incentives concept by offering free services such as PCR tests, treatment, and vaccination with no repercussions for all citizens, expatriates, visitors, and residency violators [69] . Moreover, offering free sanitizers in public and private places such as restaurants and workplaces has encouraged people to increase their hand hygiene [70] . Effective public health emergency preparedness and response requires appropriate pre-event, during the event (crisis phase), and post-event (consequence phase) activities.…”
Section: Ksa Response To Covid-19 Pandemic: Mitigation Strategies By Using the Combined Modelmentioning
confidence: 99%